Brotherhood in Christ towards a Ukrainian Baptist perspective on associations of churches - Geychenko, Oleksandr (Langham Academic, 2024)
Traditional evangelical theology, with its emphasis on individual responsibility and the independence of faith communities, has often failed to offer a robust ecclesial vision for the unity of Christ's church. Engaging this reality, Dr. Oleksandr Geychenko seeks to provide a theological framework for understanding the ecclesiological nature of Ukrainian Baptist church associations. He traces the history and development of Baptist unions in Eastern Europe, examining associational practices and organisational structure, along with the theological language used to describe the role and purpose of such unions. In dialogue with the covenant theology of Paul S. Fiddes, he demonstrates that church associations should be viewed as more than pragmatic entities. Rather, they are ecclesial bodies embodying covenantal unity, committed to mutual care and participation in Christ's mission to the world.While drawing from primary sources and ecclesial practices to provide a unique and significant contribution to local theology, this study bears relevance for engaging ecumenical relations across traditions and encouraging the unity of the broader global church
Keywords: Geschichte 1880-2014; Ekklesiologie; Unionsbestrebungen; Baptisten; Ukraine; Baptists; Baptists / Doctrines; Ukraine / Church history / 20th century; Baptistes; Baptistes / Doctrines; Ukraine / Histoire religieuse / 20e siècle; Baptist; Ecclesiology